Length–weight relationships of 5 fish species from the Sine Saloum estuary, Senegal, West Africa. (13th June 2021) - Sadio, Oumar; Simier, Monique; Le Loc'h, François; Tito de Morais, Luis
Abstract: Length‐weight relationships (W = aL b ) were estimated for 5 fish species, the pearl stingray Fontitrygon margaritella (Compagno & Roberts, 1984), the West African spadefish Chaetodipterus lippei (Steindachner, 1895), the East Atlantic African spadefish Ephippus goreensis (Cuvier, 1831), the law croaker Pseudotolithus senegallus (Cuvier, 1830) and the Guinean sole Dagetichthys cadenati (Chabanaud, 1948). Fishes were collected during several scientific fishing surveys using purse seine (length 250 m, height 20 m, 14 mm mesh size) and beach seine (180 m length, 9 m height and 25 mm mesh net) conducted from April 1990 to October 2012 in the Sine Saloum estuary, Senegal. They were weighed to the nearest g and measured to the nearest mm (disc width for Fontitrygon margaritella and total length for the 4 other species). The values of parameter b in the LWR equations varied from 3.048 ( Chaetodipterus lippei ) to 3.274 ( Dagetichthys cadenati ) and the coefficient of determination (r²) varied between 0.969 ( Fontitrygon margaritella ) and 0.998 ( Chaetodipterus lippei) . In addition, new maximum lengths are proposed for Fontitrygon margaritella, Chaetodipterus lippei and Dagetichthys cadenati .